PERFORMANCE MEASUREMENT OF PUBLIC SERVICE AGENCY IN HIGHER EDUCATION INSTITUTIONS: A Balanced-Scorecard Model Approach - Slamet, Slamet; Esha, Muhammad In'am (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aims to develop a framework for measuring higher education performance as the Public Service Agency. The authors adapted one of the measurement models, namely the Balance Score Card Model. This is a qualitative study with library research type. The data collection uses literature documents related to the discussion subject. The results show that the Balanced Scorecard Model could be used to measure the performance of higher education institutions that has the mandate as the Public Service Agency. The target of the Balanced Scorecard Model is developed to measure the corporation. Corporations and public institutions have different objectives, characteristics, and philosophies. However, the model can be utilized to measure the performance of public institutions by adapting the components from each perspective. This study contributes to the development of higher education performance measurement framework serving as the Public Service Agency.